Zakat management innovation: Wakalah contract for cash flow stabilization - Muqorobin, Ahmad; Hubur, Aa; Budiman, Alwan Rifqi; Hidayah, Akmal; Yahuza, Bello Sani (Faculty of Business & Economics, Universitas Islam Indonesia, 2025)
Purpose – Zakat institutions (ZIs) face managerial inefficiencies to the extreme seasonality of zakat fitr collection, which restricts distribution to short-term consumptive aid. This study analyzes LAZISMU's